Frequency and Sensitivity of Extended Spectrum Beta-Lactamase Positive Organisms in a Secondary and Tertiary Level Hospital Network in Dhaka - Asna, Shah Md Zahurul Haque; Akhter, Shameem; Rahman, M Mushfequr; Mohammad, Najib; Hafez, MA (Journal of Enam Medical College, 2015)
Background: Extended spectrum ?-lactamase (ESBL) positive organisms are now a global health concern including in Bangladesh. These are associated with treatment failure, increased morbidity and mortality and increased health care costs. In this study, frequency of ESBL positive organisms in some health care centres in Dhaka city has been observed and their current status of antibiogram has also been observed. Objective: To observe the current status of antibiogram of ESBL positive organisms. Materials and Methods: This cross-sectional study was done in the Department of Microbiology, Bangladesh Institute of Health Sciences (BIHS) General Hospital, Dhaka, Bangladesh from March, 2012 to February, 2013. Only E. coli and Klebsiella spp. from pus and urine specimens were included in this study. Isolation, identification and antibiotic sensitivity of the organisms were done by standard procedures. Results: Organisms (Escherichia coli and Klebsiella spp.) isolated from urine and pus collected from different sites of 472 subjects were studied. Predominant organisms were Escherichia coli (82.8%) and remaining 17.2% were Klebsiella spp. ESBL positive organisms were higher in Escherichia coli (54.5%) than in Klebsiella spp. (44.4%) and higher in pus (77.0%) than in urine (49.1%) isolates. Imipenem is the most effective drug for treating ESBL positive organisms followed by colistin, tigecycline and piperacillin/tazobactam. Conclusion: Imipenem, colistin, tigecycline and piperacillin/tazobactam drugs should be kept reserved and used only when other effective drugs are not available so that emergence of resistance against these drugs is deferred. While reporting the culture and sensitivity tests, the ESBL positive organisms should be pointed out with comment like this The organisms are ESBL positive and resistant to penicillins, cephalosporins and monobactams. J Enam Med Col 2015; 5(2): 80-87